Analisis Kesulitan Guru Geografi dalam Mengidentifikasi Potensi dan Minat Belajar Siswa pada Implementasi Kurikulum Merdeka di SMAN 1 Sunggal - Nadratul Aini Lubis; Tumiar Sidauruk; Eka Suci Anja Kusumawati (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to describe the difficulties faced by Geography teachers at SMAN 1 Sunggal in identifying students' learning potential and interests during the implementation of the Merdeka Curriculum. The research uses a descriptive qualitative approach with primary data consisting of in-depth interviews and non-participant observation of two experienced Geography teachers. The research findings indicate that teachers face major constraints, including limited time for formal diagnostic assessments, a lack of practical training on diagnostic assessments, a large number of students making individual observation difficult, and the absence of adequate assessment instruments. The teacher's efforts to overcome these difficulties include a personal approach to students, behavioral observation, and varied teaching methods, although these are not yet optimal in supporting differentiated learning. This research provides important recommendations for the development of teacher training and school policies to more effectively support the assessment of student potential and interests within the context of the Merdeka Curriculum.